Inhibitory immune checkpoints beyond programmed cell death ligand 1 in Merkel cell carcinoma: abundant expression of TIGIT independent of the presence of Merkel cell polyoma virus - Toberer, Ferdinand; Winkler, Julia K.; Fernandez, Leroy Atienza; Adams, Lea; Brobeil, Alexander; Tóth, Marcell; Enk, Alexander; Becker, Jürgen C.; Lonsdorf, Anke Susanne (Acta dermato-venereologica, 2025)
Merkel cell carcinoma is a rare, aggressive skin cancer in which Merkel cell polyoma virus (MCPyV) is frequently pathogenically involved. After failure of anti-programmed cell death protein 1/programmed cell death ligand 1 immunotherapy, therapeutic options for advanced disease are limited. The contribution of the coinhibitory checkpoint molecule T cell immunoreceptor with immunoglobulin and immunoreceptor tyrosine-based inhibitory motif domain (TIGIT), a regulator of exhausted CD8+ T cells, to the immunosuppressive Merkel cell carcinoma microenvironment is understudied. This study evaluated the immunohistochemical expression of tumour (Tumor Proportion Score, TPS) and infiltrating immune cells (Immune Cell Score, ICS) for programmed cell death ligand 1, TIGIT, its high-affinity receptor CD155, and CD8 in 21 primary Merkel cell carcinoma and 6 metastases. Unlike CD155, TIGIT was abundantly expressed by tumour and immune cells and independent of the MCPyV status, determined by RT-PCR. Programmed cell death ligand 1+ immune cells were significantly increased in TIGIT TPS-positive and MCPyV-positive primary MCC along with significant intercorrelations of programmed cell death ligand 1 and TIGIT immune cell expression and CD8+ infiltrates. Programmed cell death ligand 1 IC-positivity correlated with superior disease-specific survival. The data indicate that TIGIT may contribute to local immune dysfunction in Merkel cell carcinoma, beyond programmed cell death ligand 1 and independent of MCPyV, and provide a rationale to further explore TIGIT as a potential target for Merkel cell carcinoma immunotherapy.